Pengaruh Etika Profesi Dan Gender Terhadap Profesionalisme Auditor (Survey Pada Kantor Akuntan Publik Wilayah Palembang) - Anggraini, Ika; Hendri, Edduar; Putra, Andri Eko (Universitas PGRI Palembang, 2024)
ABSTRACT This study means to decide how huge the impact of Professional Ethics and Gender on Auditor Professionalism. This study utilizes quantitative techniques. The kind of information utilized in this study is essential information. Essential information was gotten from conveying polls to 5 public bookkeeping firms in the Palembang region. The examining strategy utilized is utilizing the reason testing recipe utilizing an example got by 65 respondents involving the class of male reviewers upwards of 27 individuals and female inspectors 38 individuals. The exploration speculation testing was completed utilizing different relapse factual tests, to be specific t test or fractional test and coefficient of assurance (R2). in light of what will happen the examination found proof that the degree of expert morals meaningfully affects examiner impressive skill and orientation level affects reviewer professionalism at the Palembang Public Accounting Firm Kata Kunci : professional ethics, Gender, and auditor professionalism ABSTRAK Penelitian ini berencana untuk memahami bahwa moral dan orientasi yang baik secara bersama-sama mempengaruhi keterampilan pemegang buku yang mengesankan, sehingga penelitian ini menggunakan strategi kuantitatif. Informasi penting diperoleh dengan melakukan survei untuk mengeksplorasi organisasi. Strategi pemeriksaan yang digunakan adalah memperoleh informasi dari 65 responden 27 orang. Terlebih lagi, 38 penelitian ini menggunakan persamaan alasan pemeriksaan. Pengujian spekulasi eksplorasi menggabungkan beberapa tes kekambuhan yang dapat diukur: uji-t, uji f atau tidak lengkap, dan koefisien kepastian (R2). Mengingat apa yang terjadi, konsekuensi dari pemeriksaan menunjukkan bahwa tingkat moral ahli mempengaruhi keterampilan evaluator yang mengesankan. Kata Kunci : Etika Profesi, Gender, dan Profesionalisme Auditor